Micromethod for Identification of Anaerobic Bacteria: Design and Operation of Apparatus - Wilkins, Tracy D. (1975)
A replicator is described for transferring 48 bacterial cultures into separate wells of microtiter plates. The device was designed for determination of carbohydrate fermentation patterns of anaerobic bacteria but should be useful for other applications. A simple device for filling microtiter wells with media is also described.